2012
DOI: 10.1063/1.4754817
|View full text |Cite
|
Sign up to set email alerts
|

Energy and electromagnetism of a differential k-form

Abstract: Let X be a smooth manifold of dimension 1 + n endowed with a Lorentzian metric g. The energy tensor of a 2-form F is locally defined asIn this paper we characterize this tensor as the only 2-covariant natural tensor associated to a Lorentzian metric and a 2-form that is independent of the unit of scale and satisfies certain condition on its divergence. This characterization is motivated on physical grounds, and can be used to justify the Einstein-Maxwell field equations.More generally, we characterize in a sim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Casting the classical EM field theory into a differential forms formalism originates in the pioneering works [51]- [54] and was elaborated upon in [55]. Differential forms were applied in EM over a very broad range, starting with basic formulations [56] up to high-level studies [57]. The main difference with respect to the prevalent, vector mathematic representation of EM quantities is dropping the continuous r-dependence, which was unwarranted in this case, and replacing it with a small integrals interpretation.…”
Section: Differential Forms Representationmentioning
confidence: 99%
“…Casting the classical EM field theory into a differential forms formalism originates in the pioneering works [51]- [54] and was elaborated upon in [55]. Differential forms were applied in EM over a very broad range, starting with basic formulations [56] up to high-level studies [57]. The main difference with respect to the prevalent, vector mathematic representation of EM quantities is dropping the continuous r-dependence, which was unwarranted in this case, and replacing it with a small integrals interpretation.…”
Section: Differential Forms Representationmentioning
confidence: 99%
“…[20][21][22]), p-form electrodynamics (e.g. [23,24]), as a natural particular case of the theory. It is observed that current formulations of p-form electrodynamics use additional geometric structure and consider smooth fields.…”
Section: (C) Outlinementioning
confidence: 99%
“…[20][21][22]), p-form electrodynamics (e.g. [23,24]), as a natural particular case of the theory. It is observed that .…”
Section: (C) Outlinementioning
confidence: 99%
“…In [5] it is proved, under some additional assumptions, that such a T has to be (E, ∂F ), where E ab := −(F a i F bi − 1 4 F ij F ij g ab ) stands for the energy tensor of the 2-form F = dA. As it is well-known, this source equation (E, ∂F ) is locally variational.…”
Section: Hence Theorem 12 Says That If T Is a Locally Variational Ementioning
confidence: 99%
“…On the other hand, let E ab := − F a i F bi − 1 4 F ij F ij g ab be the usual energy tensor of the 2-form F = dA. This tensor E can be characterized as the only 2-tensor that is natural, satisfies div g E = −i ∂F F and fulfils certain homogeneity and normalization conditions ( [5]).…”
Section: Noether's Second Theorem On Natural Bundlesmentioning
confidence: 99%